The Oxford handbook of crime and public policy - Tonry, Michael H. (Oxford : Oxford University Press, 2009)
This handbook offers a comprehensive examination of crimes as public policy subjects to provide an authoritative overview of current knowledge about the nature, scale, and effects of diverse forms of criminal behaviour and of efforts to prevent and control them.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Crime; Crime prevention; Criminal justice, Administration of; True Crime; Social services & welfare, criminology